Characters-Based Collaborative Learning Model: Its Impacts on Students’ Attitude and Achievement - Rahdiyanta, Dwi; Hargiyarto, Putut; Asnawi, Asnawi (Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
This study determined the impacts of the implementation of characters-based collaborative learning model on the students’ attitudes and achievement in the course of machining process. This experimental study was conducted in the fitting and machining workshop at the Department of Mechanical Engineering Education, Faculty of Engineering, Universitas Negeri Yogyakarta. The population consisted of the students who were taking the course of Complex Machining Process totaling 85 students. The samples included 33 students who were determined by purposive sampling technique. The experiment was carried out by the posttest-only control design. The instrument validation was conducted by expert judgment. The data in this study were analyzed using descriptive analysis and t-test with significance level of 0.05. The results revealed that: (1) the attitude of the students in the model class was better than the conventional class, and (2) the students of the model class performed better achievement in the course of Machining Process.